The PREHAAAB Trial: Multimodal prehabilitation for patients awaiting open abdominal aortic aneurysm repair – A study protocol for an international randomized controlled trial - Miquel Coca-Martinez; Robert J. Doonan; Chelsia Gillis; Kent Mackenzie; Daniel I. Obrand; Jason P. Bayne; Oren K. Steinmetz; Elie Girsowicz; Manuel Lopez-Baamonde; Samuel Jessula; Xavier Yugueros; Graciela Martínez-Pallí; et al. (PLoS ONE, 2025)
Background Patients undergoing open abdominal aortic aneurysm (AAA) repair remain at high risk for postoperative complications, particularly when presenting with limited baseline functional capacity. Prehabilitation, encompassing physical, nutritional, and psychological optimization before surgery, may improve outcomes in this population. However, evidence is limited in the context of open AAA repair. Objective To evaluate the effectiveness of a multimodal prehabilitation program in reducing the incidence of postoperative complications in patients undergoing open AAA repair. Methods This is a multicenter, international, randomized controlled trial. Eligible participants include adults scheduled for elective open AAA surgery. A total of 152 participants will be randomized 1:1 to receive either standard preoperative care or a 6-week multimodal prehabilitation program consisting of supervised exercise training, individualized nutritional support, and psychological counseling. The primary outcome is the rate of postoperative complications as measured by the Comprehensive Complication Index (CCI). Secondary outcomes include length of hospital stay, and readmission rates, changes in functional capacity, health-related quality of life and anxiety & depression. Data will be analyzed on an intention-to-treat basis. The study complies with SPIRIT 2013 guidelines and is registered at ClinicalTrials.gov (NCT05756283). Discussion This trial will address a significant evidence gap regarding preoperative optimization in open abdominal aneurysm surgery. Findings will inform best practices for reducing morbidity in this high-risk population and contribute to enhanced recovery strategies in vascular surgery. Trial registration [NCT05756283]